PERCEVEJOS (HEMIPTERA: HETEROPTERA) COLETADOS EM ACEROLEIRA (MALPIGHIA GLABRA L.) EM JABOTICABAL, SP - Michelotto, M.d. (2022)
IN JABOTICABAL, SP, BRAZIL. The objective of this work was to verify the occurrence of stinkbugs on Barbados cherry plants (Malpighia glabra L.), between 2002 and 2004, in Jaboticabal, State São Paulo, Brazil. Eleven species were colected: 7 species of Coreidae, 3 of Pentatomidae and 1 of Scutelleridae. The species Acanthocephala sp., Hyalynemus sp., Machtima crucigera (Fabricius), Euschistus atrox (Westwood), Loxa deducta and Piezodorus guidinii (Westwood) are reported for first time on Barbados cherry plants.